The Analysis of the Implementation of Standard Operational Procedures (Sop) in BCD Companies - Jennah_Marsha24 (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze the implementation of Standard Operating Procedures (SOP) in BCD Company, identify the obstacles faced and propose solutions to improve organizational performance. Using qualitative descriptive methods, data collection was carried out through direct observation, literature studies, documentation and in-depth interviews with employees directly involved in the company’s operations. The results show that although SOPs already exist in BCD Company, their implementation is still less than optimal. The main challenges faced are limited staff understanding of existing SOPs, lack of comprehensive socialization and training, and unclear procedures for certain situations. In addition, inconsistent evaluation and monitoring result in some procedures being forgotten or incorrectly followed, resulting in inefficiencies and inconsistencies in the organization. Address these issues, periodic evaluation of SOP implementation is recommended to ensure compliance and identify gaps. A comprehensive training program should be developed to improve employee understanding of SOPs and their importance in ensuring operational efficiency, accuracy and consistency. In addition, fostering a culture of continuous feedback and collaboration among employees is also recommended as a way to refine and improve SOPs. By addressing these challenges systematically, BCD Company can maximize the effectiveness of its SOP implementation. This will not only improve operational efficiency but also contribute to better overall organizational performance, ensuring that the company achieves its strategic goals more effectively.